Class Iii Skeletal Base In Malay Population: Characterisation Of Skeletal Phenotypes And Association With Familial Inheritance - Ran, Arron Lim Yan (2023)
Class III skeletal discrepancy results from the disproportionate growth of the maxilla and mandible. Dentofacial skeletal features vary significantly between different ethnicities and Class III malocclusions, which are difficult to treat, were highly prevalent in Malaysians compared to other races. In the Malay population, the skeletal phenotypes of Class III skeletal base have never been investigated. Therefore, the general objective of this study was to investigate and characterise the different Class III skeletal phenotypes in a racially homogenous adult Malay population and determine their association with familial inheritance. This study also sought to determine the prevalence of Class I, Class II and Class III skeletal base among Malay patients attending the Advanced Medical and Dental Institute (AMDI) orthodontic clinic, determine the precursor for genetic analysis using multivariate reduction method and ascertain the proportion of familial occurrence of Class III skeletal base.